Pengaruh Religiusitas, Kepercayaan dan Lokasi BAZNAS Kabupaten Bone terhadap Keputusan Masyarakat Muslim Membayar Zakat - Adriani, Adriani; Anwar, Nurfiah; Muslihati, Muslihati (ALSYS, 2023)
This thesis is entitled The Influence of Religiosity, Belief and Location of Bone Regency BAZNAS on the Muslim Community's Decision to Pay Zakat. This research aims to see the extent of the influence of religiosity, belief and location on the Muslim community's decision to pay zakat at BAZNAS Bone Regency. The method used in this research is a quantitative method. The number of samples in this study was 383 respondents. Data collection techniques in this research used questionnaire and documentation techniques. The results of this research show that the religiosity variable (X1) partially has no influence on the Muslim community's decision to pay zakat, while the Trust (X2) and Location (X3) variables partially have a positive influence on the community's decision to pay zakat with a significance value of less than 0.05.